Ghana : 2011 Article IV Consultation and Third and Fourth Reviews Under the Arrangement Under the Extended Credit Facility, Requests for Waiver of Nonobservance of Performance Criteria and Modification of Performance Criteria, and Rephasing of Disbursements-Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Ghana. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Ghana showed strong growth underpinned by high commodity export prices, the start of oil production, and strong non-oil activity. Executive Directors welcomed this development, and stressed that monetary policy implementation will need to remain vigilant. Directors welcomed the recent approval of an oil revenue management bill. They appreciated measures taken to address stability risks in the banking sector identified by the Financial Sector Assessment Program (FSAP) Update. They emphasized that the focus of the Extended Credit Facility (ECF)-supported program is to expand economic growth through prudent macroeconomic policies supported by structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet